Life cycle assessment and material flow analysis of road and rail infrastructure assets – A critical review - Soroosh Ataee; André Stephan (Cleaner Environmental Systems)
Transport infrastructure assets are essential for society, but they also usually result in significant environmental effects. To assess and reduce these effects, various methods such as life cycle assessment (LCA) and material flow analysis (MFA) have been applied to transport infrastructure assets. This paper provides a comprehensive review of the current research on the application of LCA and MFA to transport infrastructure assets, focusing on energy and greenhouse gas emissions. Considering 640 publications, the paper identifies the aims and drivers of the studies, the scope and boundaries of transport infrastructure assets, tools and data sources used for LCA and MFA, and the key findings and limitations of previous studies and models. The paper also highlights the research gaps and future research directions, such as integrating LCA and MFA, expanding the scope of transport infrastructure assets considered, improving the data quality and availability, and addressing the uncertainties and trade-offs in the assessment. The paper aims to provide a critical overview of the state-of-the-art methods and knowledge on the environmental assessment of TIA, and to suggest ways to improve the performance of TIA in the future.